Revitalization of a Forward Genetic Screen Identifies Three New Regulators of Fungal Secondary Metabolism in the Genus Aspergillus - Brandon T. Pfannenstiel (American Society for Microbiology, 2017)
ABSTRACT The study of aflatoxin in Aspergillus spp. has garnered the attention of many researchers due to aflatoxin’s carcinogenic properties and frequency as a food and feed contaminant. Significant progress has been made by utilizing the model organism Aspergillus nidulans to characterize the regulation of sterigmatocystin (ST), the penultimate precursor of aflatoxin. A previous forward genetic screen identified 23 A. nidulans mutants involved in regulating ST production. Six mutants were characterized from this screen using classical mapping (five mutations in mcsA) and complementation with a cosmid library (one mutation in laeA). The remaining mutants were backcrossed and sequenced using Illumina and Ion Torrent sequencing platforms. All but one mutant contained one or more sequence variants in predicted open reading frames. Deletion of these genes resulted in identification of mutant alleles responsible for the loss of ST production in 12 of the 17 remaining mutants. Eight of these mutations were in genes already known to affect ST synthesis (laeA, mcsA, fluG, and stcA), while the remaining four mutations (in laeB, sntB, and hamI) were in previously uncharacterized genes not known to be involved in ST production. Deletion of laeB, sntB, and hamI in A. flavus results in loss of aflatoxin production, confirming that these regulators are conserved in the aflatoxigenic aspergilli. This report highlights the multifaceted regulatory mechanisms governing secondary metabolism in Aspergillus. Additionally, these data contribute to the increasing number of studies showing that forward genetic screens of fungi coupled with whole-genome resequencing is a robust and cost-effective technique. IMPORTANCE In a postgenomic world, reverse genetic approaches have displaced their forward genetic counterparts. The techniques used in forward genetics to identify loci of interest were typically very cumbersome and time-consuming, relying on Mendelian traits in model organisms. The current work was pursued not only to identify alleles involved in regulation of secondary metabolism but also to demonstrate a return to forward genetics to track phenotypes and to discover genetic pathways that could not be predicted through a reverse genetics approach. While identification of mutant alleles from whole-genome sequencing has been done before, here we illustrate the possibility of coupling this strategy with a genetic screen to identify multiple alleles of interest. Sequencing of classically derived mutants revealed several uncharacterized genes, which represent novel pathways to regulate and control the biosynthesis of sterigmatocystin and of aflatoxin, a societally and medically important mycotoxin.